Plant breeding reviews : Volume 39 - Janick, Jules, 1931- (Hoboken, NJ : Wiley Blackwell, 2015)
Plant Breeding Reviews presents state-of-the-art reviews on plant genetics and the breeding of all types of crops by both traditional means and molecular methods. Many of the crops widely grown today stem from a very narrow genetic base; understanding and preserving crop genetic resources is vital to the security of food systems worldwide. The emphasis of the series is on methodology, a fundamental understanding of crop genetics, and applications to major crops. It is a serial title that appears in the form of one or two volumes per year.
Charles W. Stuber: Maize Geneticist and Pioneer of Marker-Assisted Selection -- Plant Mutation Breeding: Current Progress and Future Assessment -- Recent Advances in Sorghum Biofortification Research -- Breeding Tropical Vegetable Corns --Maize breeding in the United States -- The history, development, and importance of the New Mexican pod-type chile pepper to the United States and world food industry -- Fruit domestication in the Near East -- The Geneva apple rootstock breeding program.
Includes index.
Print version record.
Keywords: Plant breeding; Plant breeding; Plant genetics; Plant propagation; Plant breeding; SCIENCE / Life Sciences / Botany; Electronic books